2019
DOI: 10.5296/jbls.v10i1.14022
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Quality of Raw Beef and Chevon From Selected Markets in Cape Coast, Ghana

Abstract: This study assessed microbial quality of raw beef and chevon (goat meat) from selected meat retail shops in Abura, Kotokuraba and Science markets in Cape Coast, Ghana. Stock solutions from beef and chevon were analyzed on nutrient agar, MacConkey agar, and potato dextrose agar media using microbiological procedures. Results revealed that beef from Kotokuraba market was the most contaminated with mean highest bacterial counts of 1.15x108 and 9.40x107 cfu/ml in nutrient agar and MacConkey agar media, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Moreover, studies on the spread of E. coli among meats, humans and their environment in Ghana are limited. Studies have also shown that the manner in which animals are handled prior to slaughter, during slaughter and post-slaughter makes meat and their related samples potential sources of foodborne pathogens [26][27][28][29][30][31][32]. In addition, the sale of meats and meat products is sometimes conducted in open markets and by roadsides without adherence to strict hygiene [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies on the spread of E. coli among meats, humans and their environment in Ghana are limited. Studies have also shown that the manner in which animals are handled prior to slaughter, during slaughter and post-slaughter makes meat and their related samples potential sources of foodborne pathogens [26][27][28][29][30][31][32]. In addition, the sale of meats and meat products is sometimes conducted in open markets and by roadsides without adherence to strict hygiene [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“… 26 Staphylococcus spp. was the second most isolated bacterium, reported by 44% (32/72) of the studies 23 , 25 , 27 - 29 , 31 , 33 , 35 - 39 , 41 , 44 , 48 , 49 , 52 , 54 , 55 , 57 , 62 , 65 - 67 , 70 , 71 , 74 , 75 , 79 - 82 ; 19 of these 32 studies specifically reported on Staphylococcus aureus , with individual prevalence ranging from 4% to 97%. 23 , 25 , 27 - 29 , 31 , 33 , 41 , 48 , 57 , 65 - 67 , 70 , 71 , 74 , 75 ,…”
Section: Resultsmentioning
confidence: 99%
“…This result is also in aligning with study done in Gondar, Ethiopia. However, resistance to Ampicillin is much higher than in Bahir dar(23.8%) [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. In other way the study revealed an overall Shigella prevalence of 2.67% which is higher than study done in Jimma,Ehiopia but, lower than in Karachi,Pakistan and Gondar [7,68,79].However, similarly lower rate of isolation was reported from Ebony,Nigeria [1].…”
Section: Discussionmentioning
confidence: 99%